Clinical and molecular analyses of isolated central congenital hypothyroidism based on a survey conducted in Japan - Nao Shibata; Chikahiko Numakura; Takashi Hamajima; Kenichi Miyako; Ikuma Fujiwara; Jun Mori; Akihiko Saitoh; Keisuke Nagasaki (Endocrine Journal)
Central congenital hypothyroidism (CH) can occur as an isolated deficiency or as part of combined pituitary hormone deficiency. Unlike primary CH, central CH cannot be detected by newborn screening (NBS) using dry filter paper blood TSH levels, and early diagnosis remains challenging. In this study, the clinical and genetic backgrounds of patients with isolated central CH were determined through a questionnaire-based survey among members of the Japanese Society for Pediatric Endocrinology. The known causes of isolated central CH were studied in 14 patients, including six with previously reported patient data. The results revealed IGSF1 and TBL1X pathogenic variants in nine and one patient, respectively. All six patients with low free thyroxine (FT4) levels detected in NBS carried IGSF1 pathogenic variants. Five patients with isolated central CH diagnosed after 3 months of age were variant-negative, except for one female patient with a heterozygous IGSF1 variant. Two of the four variant-negative patients and a variant-positive patient were diagnosed with pituitary hypoplasia. One and two patients with IGSF1 variant had obesity and intellectual disability, respectively. Left amblyopia was identified in the patient with a TBL1X variant. The study revalidated that IGSF1 variants comprise the most frequent pathogenic variant in patients with isolated central CH in Japan. The neonatal period is the optimal time for the diagnosis of central CH, particularly IGSF1 abnormalities, and the introduction of T4 screening should be considered in the future, taking cost-effectiveness into consideration.